(untitled) (Ciudades, 2017)
Regional planning is a growing subject that has not yet reached maturity in Portugal. This article presents a brief reflection concerning his problems, from the capital region case study. After an introduction to the country’s administrative framework and his planning practices, it summarizes some of the current spatial dynamics and identifies the key issues to improve the governance of the Lisbon metropolitan area. From this perspective, it argues for a larger partnership between the technical and political dimensions of regional planning, which requires not only institutional reforms, but also progresses in the operational issues, participation, strategy and cooperation.